2010
DOI: 10.1159/000326564
|View full text |Cite
|
Sign up to set email alerts
|

BDNF/TrkB Content and Interaction with Gastrin-Releasing Peptide Receptor Blockade in Colorectal Cancer

Abstract: Objective: Neurotrophin and neuropeptide pathways are emerging targets in cancer. Here we show that brain-derived neurotrophic factor (BDNF) and its receptor, TrkB, are present in colorectal cancer and that BDNF levels are increased in tumors compared to nontumor tissue. In addition, we investigate the role of BDNF in influencing the response of colorectal cancer cells to inhibition of gastrin-releasing peptide receptors (GRPR). Methods: Fresh-frozen sporadic colorectal adenocarcinoma specimens and adjacent no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 74 publications
1
49
1
Order By: Relevance
“…BDNF has been shown to be expressed in 93.3% of CRC tumours [17] and expression levels were observed to be higher in tumour tissue than non-neoplastic tissue [17,18]. Furthermore, multiple CRC cell lines have been shown to produce endogenous BDNF and together with TrkB an autocrine signalling loop exists in these cells that promotes cell proliferation and survival [18].…”
Section: Introductionmentioning
confidence: 99%
“…BDNF has been shown to be expressed in 93.3% of CRC tumours [17] and expression levels were observed to be higher in tumour tissue than non-neoplastic tissue [17,18]. Furthermore, multiple CRC cell lines have been shown to produce endogenous BDNF and together with TrkB an autocrine signalling loop exists in these cells that promotes cell proliferation and survival [18].…”
Section: Introductionmentioning
confidence: 99%
“…The high expression level of BDNF is of great concern in cancer research. BDNF is found to be elevated in diverse tumors, including in hepatocellular carcimona [13], melanoma [14], and colorectal cancer [15], but not in nontumorous tissues or normal cell lines. Such previous researches suggest that BDNF may be involved in the development and progression of these malignancies.…”
mentioning
confidence: 99%
“…We and others have reported that BDNF and TrkB levels are increased in CRC tumors [6,7]. Treating human CRC cells with an experimental anticancer peptide increases the mRNA expression, protein content, and secretion of BDNF, through a mechanism that depends on EGFR activity.…”
mentioning
confidence: 76%
“…Treating human CRC cells with an experimental anticancer peptide increases the mRNA expression, protein content, and secretion of BDNF, through a mechanism that depends on EGFR activity. The increase in BDNF results in a compensatory response that rescues CRC cell proliferation and survival [6]. Importantly, BDNF protects against the anti-proliferative effect of cetuximab in a human CRC cell line, whereas a TrkB inhibitor can sensitize the cells to a low dose of cetuximab [8].…”
mentioning
confidence: 99%